Teori, Genre, Jenis Sastra Anak - Alfina Almunawar; Rahma Ashari Hamzah; Sri Sugiarti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
the importance of children's literature in supporting the development of literacy, character, and imagination in the digital era. Children's literature has unique characteristics and must be adapted to the world and stage of psychological development of children. As prospective elementary school educators, understanding the theory and genre of children's literature is important in selecting and delivering appropriate reading materials. This study examines the theory of children's literature according to experts, the classification and characteristics of various genres of children's literature such as fairy tales, fables, myths and legends, children's poetry, picture stories, children's novels, fantasy, and realistic fiction. Each genre is discussed by prioritizing the educational and moral functions contained, and is equipped with examples of relevant children's literature. With this approach, this paper aims to provide prospective teachers with a comprehensive understanding of the use of children's literature in an interesting and meaningful learning process.